Geochemistry of I-type Volcanic Arc Granitoid From Tanggamus Regency, Southern Sumatra - Ronaldo Irzon; Kurnia Kurnia; Muhammad Firdaus; Eko Yulianto; Firdaus Djabar (Journal of Mathematical and Fundamental Sciences, 2023)
Granitoid intrusion of several provinces on Sumatra is correlated with Southeast Asia tectonics that have occurred since the Permian. Granites from several volcanic arc provinces are located along the western part of Sumatra Island and are found near Bukit Barisan. This study describes the geochemical character of granitoid from the Tanggamus region and its surroundings near the Bukit Barisan cluster. After megascopic description in the field, major oxides, trace elements, and rare earth elements in rock samples were measured using X-ray fluorescence and inductively coupled plasma-mass spectrometry devices. The samples were intermediate to acidic intrusive rocks with SiO2 ranging between 61.35% and 75.29%. The rocks can be described as diorite to granodiorite and were formed as a result of subduction processes. The granitic rock samples showed I-type features of A/CNK value <1.1, volcanic arc granite affinity, K2O/Na2O ratio, and magnesian properties. The total rare earth content was medium with an average of 43.97 ppm. The similarity of the rare earth normalized diagram against the chondrite value indicates that the samples come from an identical origin.